THE ROLE OF RELIGIOUS EDUCATION IN SHAPING THE CHARACTER OF LAW STUDENTS - Ali Mansur (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2025)
This study examines the role of Religious Education in shaping the character of law students, emphasizing the urgent need for them to acquire not only intellectual competence but also moral integrity grounded in religious values. A descriptive qualitative approach was used, with data collected through interviews, participant observation, and document analysis involving students and lecturers of Religious Education courses. Data were analyzed using Miles and Huberman’s interactive model, including reduction, display, and conclusion drawing, with triangulation applied to ensure validity. The findings show that Religious Education significantly contributes to four key values: honesty, responsibility, justice, and multicultural awareness. Honesty underpins academic and professional integrity, while responsibility develops discipline and accountability. Justice provides an ethical orientation beyond formal law, and multicultural awareness fosters tolerance and inclusivity. Together, these values form the ethical foundation required for integrity-based legal professionalism. This research highlights that Religious Education is not merely a normative subject but a transformative instrument for character formation. It suggests that Religious Education curricula should be systematically integrated with legal ethics, multiculturalism, and contemporary challenges to prepare law graduates who are not only intellectually competent but also morally grounded professionals